Changes in the Livelihood System of the Kerang Dayo Village Community from Loggers to Oil Palm Farmers (2010-2020) - Fathurrahman; Rochgiyanti; Sulistia, Yunarti; Yahya, Daud; Yuliantri, Rhoma Dwi Aria (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research aims to uncover and analyze changes in the livelihoods of the Kerang Dayo Village community in the period 2010-2020, focus on the transition from livelihoods as loggers to farmers palm oil. This research uses a historical methodology approach to understand the factors that influence this transformation. Primary data was obtained through interviews with residents of Kerang Dayo Village who work as palm oil farmers, while secondary data was obtained from the village fund budget, the village government agency, and the local government. statistical center, and related historical sources. The research results show that there are several factors that make the community in Kerang Dayo Village switched professions from loggers to palm oil farmers. In the past, wood was the source of main source of livelihood, but over time the supply of timber commodities in the forest has increased. restricted forest area. As a result of this, it encouraged logging workers looking for alternative jobs by becoming palm oil farmers. Interest people of Kerang Dayo Village become palm oil farmers because of the benefits that obtained is greater than being a woodchopper.